KONTRIBUSI KEMAMPUAN NUMERIK DAN SPASIAL TERHADAP HASIL BELAJAR FISIKA SISWA - Ngadimin Ngadimin; Fira Sanirin (JURNAL FISIKA EDUKASI, 2015)
Ability is an internal factors that determine the success of people works. This study aims to determine whether there is a contribution between numerical and spatial abilities of the students' learning success . This study is a preliminary study conducted towards 25 students of class XI SMAN 5 Banda Aceh . Methods of data collection used written test to measure the abilities of numerical and spatial and utilize the documentation to get students’ physics achievement. Data were analyzed using multiple correlation techniques. According to  processing and analysis of research data,then be concluded as following:  numerical ability contributes on Physics achievement; spatial ability contributes on Physics achievement; numerical and spatial abilities contribute to students’ achievement.